Designing a Musical Instrument: Enlivening Theory Through Practice-Based Research. - Sylleros, Alvaro; de la Cuadra, Patricio; Cádiz, Rodrigo (Design Issues)
The article discusses the design of the electronic musical instrument known as the Arcontinuo. Topics discussed include quality, the concept of interaction developed by Francisco Varela, and the connection between interaction and identity. The article also explores the concept of narrative identity, the design research process, and the process by which all of these various concepts were put to use in order to create a working prototype of the Arcontinuo electronic musical instrument. Various diagrams are provided to illustrate the design process.